1996
DOI: 10.2172/188919
|View full text |Cite
|
Sign up to set email alerts
|

Improved techniques for fluid diversion in oil recovery. Final report

Abstract: This report describes work performed during the third and final year of the project, 'Tmproved Techniques for Fluid Diversion in Oil Recovery." This project was directed at reducing water production and increasing oil recovery efficiency. In the United States, more than 20 billion barrels of water are produced each year during oilfield operations. An average of 7 barrels of water are produced for each barrel of oil. Today, the cost of water disposal is typically between $0.25 and $0.50 per bbl. Therefore, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 10 publications
1
49
0
Order By: Relevance
“…[124][125][126][127][128]155,156 That is, they are NOT super-polymer flooding agents. In particular, researchers from the University of Kansas 125,126 , the University of TX 124 , and New Mexico Tech 156,157 found that resistance factors (effective viscosities) provided by aluminum-citrate-HPAM colloidal dispersion gels within cores (i.e., beyond the inlet core section) were the same as those provided by polymer solution alone (i.e., containing no crosslinker). This observation suggests that either the gel particles were too small to interact significantly with pore throats or the crosslinking reaction did not take place to a significant extent.…”
Section: Laboratory Results Many Previous Lab Tests Show No Effect Ofmentioning
confidence: 99%
See 3 more Smart Citations
“…[124][125][126][127][128]155,156 That is, they are NOT super-polymer flooding agents. In particular, researchers from the University of Kansas 125,126 , the University of TX 124 , and New Mexico Tech 156,157 found that resistance factors (effective viscosities) provided by aluminum-citrate-HPAM colloidal dispersion gels within cores (i.e., beyond the inlet core section) were the same as those provided by polymer solution alone (i.e., containing no crosslinker). This observation suggests that either the gel particles were too small to interact significantly with pore throats or the crosslinking reaction did not take place to a significant extent.…”
Section: Laboratory Results Many Previous Lab Tests Show No Effect Ofmentioning
confidence: 99%
“…In other cases, 155,156 CDG gelants were found to penetrate into sand packs or sandstone and ultimately provide significant residual resistance factors. However, relatively short gelation times (less than one day) preclude deep penetration into reservoirs (i.e., over the course of weeks or months).…”
Section: Laboratory Results Many Previous Lab Tests Show No Effect Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…65 We wondered if the disproportionate permeability reduction varies with core length. To answer this question, we performed an oil-water experiment in a 2-ft Berea core.…”
Section: Oil-water Experiments In a 2 --Berea Corementioning
confidence: 99%